1993
DOI: 10.1524/ract.1993.63.special-issue.87
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Technetium with Humic Acid

Abstract: The complexation of technetium with well characterized humic acid, which was extracted from one of the Gorleben groundwaters in northem Germany, was studied. It was found that technetium humate was produced as a brownish-black precipitate by addition of Sn^^ as a reductant in a mixture Solution of pertechnetate and humic acid at pH 4 in 0.1 mol P' NaC104. This precipitate could be distinguished from the TCO2 with respect to the dissolution behavior at higher pH. The produced amount of the formed technetium hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 3 publications
1
23
0
1
Order By: Relevance
“…The exact nature of the interacting Tc(IV) species is unknown and can range from monomeric to polynuclear forms. These measurements are the first direct Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/28/15 3:40 PM indications of the interaction between Tc(IV) species and humic substances in neutral to alkaline reducing environments, and are complementary to the observations of Tc(III) interaction with humic substances by Sekine et al [4] in acid pH.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The exact nature of the interacting Tc(IV) species is unknown and can range from monomeric to polynuclear forms. These measurements are the first direct Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/28/15 3:40 PM indications of the interaction between Tc(IV) species and humic substances in neutral to alkaline reducing environments, and are complementary to the observations of Tc(III) interaction with humic substances by Sekine et al [4] in acid pH.…”
Section: Discussionsupporting
confidence: 62%
“…Under oxidising conditions, technetium is present as pertechnetate (TcO 4 − ), a highly soluble, anionic species, that does not sorb significantly on minerals or sediments [1]. Under suitable reducing conditions, and especially in the presence of a reducing solid phase, which acts as an electrondonor, TcO 4 − is reduced to probably Tc(IV). Because Tc(IV) is easily hydrolysed, a surface precipitate is formed [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Sekine et al (5) concluded by an indirect measurement that, in the presence of humic acids, Tc(III) species were formed and associated with the humic acids. But these latter experiments were made at pH < 4 and in the absence of HCO3 -.…”
Section: Introductionmentioning
confidence: 99%
“…La sorption du technétium est corrélée principalement aux teneurs en carbone organique, en oxydes de fer et d'aluminium et en argile des sols (Gu et Schulz, 1991). Les formes réduites du technétium forment des complexes très stables avec la matière organique, en particulier avec les acides humiques (Sekine et al, 1997 ;Henrot, 1989 ;Stalmans et al, 1996). Le technétium est ainsi majoritairement présent dans les horizons organiques du sol.…”
Section: Technétiumunclassified